Deleuze and Guattari : aesthetics and politics - Porter, Robert, 1972- (Cardiff : University of Wales Press, 2009)
This book examines the relationship between aesthetics and politics based on the philosophies of Gilles Deleuze (1925-1995) and Pierre-Felix Guattari (1930-1992), most famous for their collabarative works Anti-Oedipus (1972) and A Thousand Plateaus (1980).
1 Language and Literature; 2 Painting; 3 Architecture; Conclusion; Notes; Bibliography; Index; Acknowledgements; Introduction
Includes bibliographical references and index.
Print version record.
English.
JSTOR
Keywords: Deleuze, Gilles, -- 1925-1995.; Guattari, Félix, -- 1930-1992.; Deleuze, Gilles, -- 1925-1995; Guattari, Félix, -- 1930-1992; Aesthetics; Political science -- Philosophy; PHILOSOPHY -- History & Surveys -- Modern; PHILOSOPHY -- Aesthetics; Aesthetics; Political science -- Philosophy